The end of cohesion? Revisiting social fragmentation and neighbourhood crime in Argentine shantytowns - Miguez, Daniel Pedro (2016)
Rising crime rates have been a growing concern in Argentina since the 1990s. A significant body of research has associated this crime rise with the fragmentation of social bonds and forms of internal cohesion in urban areas affected by a high concentration of unemployment and poverty by income resulting from neoliberal structural reforms. Based on data from a survey conducted between 2004 and 2006, this paper’s aim is to provide some new insights to this issue by measuring the presence and extension of networks based on mutual trust and reciprocity and estimating the incidence of conflict and crime in Argentine shantytowns. These estimations suggest that the social fragmentation thesis requires certain qualifications and enable some additional hypotheses about how neoliberal policies affected the internal forms of coexistence among shantytown dwellers.